Effect of Esophageal Endoscopic Submucosal Dissection on Motility and Symptoms: A Prospective Study - Tsutomu Takeda; Kenshi Matsumoto; Akihito Nagahara; Hiroyuki Komori; Yoichi Akazawa; Yuta Nakagawa; Kentaro Izumi; Kohei Matsumoto; Hiroya Ueyama; Yuji Shimada; Daisuke Asaoka; Mariko Hojo; et al. (Gastroenterology Research and Practice)
Background. Endoscopic submucosal dissection (ESD) of esophageal tumors can cause stenosis, yet the effect of esophageal ESD on motility remains unclarified. This study aimed to compare esophageal motility and symptoms, before and after ESD, using high-resolution manometry (HRM) and symptom scoring. Methods. Twenty-eight patients with 35 cT1a cancers were prospectively enrolled between December 2014 and February 2016. Pre- and post-ESD symptom score and HRM were recorded. Based on circumferential resection (CR), patients were divided into group A (n=17, <2/3 CR) or B (n=11, 2/3 CR or greater). HRM parameters evaluated were distal contractile integral (DCI), contractile front velocity (CFV), intrabolus pressure, integrated relaxation pressure, distal latency, and peristaltic breaks. Results. Symptom scores worsened after ESD in 8/11 patients in group B, and 0/17 patients in group A. There was no significant difference in any HRM parameter after ESD in the whole study group but mean DCI tended to increase (p=0.07). In group B, DCI increased significantly after ESD (p=0.04), and CFV tended to decrease after ESD (p=0.08). Conclusions. DCI tended to increase after esophageal ESD. ESD affected the symptom score and esophageal motility in cases with 2/3 CR or greater. This trial is registered with UMIN000015829.